2020
DOI: 10.1177/1178646920927380
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Serotonin in Laying Hens (Gallus gallus domesticus) With and Without Foot pad Dermatitis

Abstract: The aim of this study was to investigate whether plasma serotonin (5-hydroxytryptamine [5-HT]) was associated with the presence of foot pad dermatitis (FPD) in laying hens. FPD birds (n = 20) and healthy individuals (n = 22) were included. Plasma 5-HT was investigated. FPD laying hens showed significantly higher 5-HT levels (median = 6 µmol/L) compared with healthy individuals (median = 4.28 µmol/L, P < .001). When present, FPD were scored as either 1 (n = 12) indicating mildly to moderately abnormal or 2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Nevertheless, the present study has found that adding PHE reduced carcass yield, which could be explained by the fact that excess PHE interferes with the transport of other amino acids, particularly tryptophan, from the blood-brain barrier and reduces serotonin production [28]. The neuromodulator serotonin is involved in a variety of physiological processes such as feeding behavior [51]. Also, oversupply of one amino acid may interfere with the absorption of other amino acids, leading to a nutritional imbalance or deficiency [52].…”
Section: Discussionmentioning
confidence: 56%
“…Nevertheless, the present study has found that adding PHE reduced carcass yield, which could be explained by the fact that excess PHE interferes with the transport of other amino acids, particularly tryptophan, from the blood-brain barrier and reduces serotonin production [28]. The neuromodulator serotonin is involved in a variety of physiological processes such as feeding behavior [51]. Also, oversupply of one amino acid may interfere with the absorption of other amino acids, leading to a nutritional imbalance or deficiency [52].…”
Section: Discussionmentioning
confidence: 56%